ANEMIA PADA IBU USIA 17-35 TAHUN DI DAERAH ‘REPLETE’ ENDEMIK DEFISIENSI IODIUM - Budiman, Basuki; Dewi, Rosmala; Muljati, Sri (PERSATUAN AHLI GIZI INDONESIA, 2007)
ANEMIA OF CHILD BEARING AGE MOTHERS 17-35 YEARS OF AGE IN ENDEMIC IODINE ‘REPLETE’ AREAIron Deficiency Anemia (IDA) as well as Iodine Deficiency Disorder (IDD) both have adverseeffects on cognitive and neuropsychomotor, and adverse pregnant outcomes. Both iron andiodine have role on nuero development. Iron interact with iodine through the activity of thyroidperoxidase (TPO), an iron-dependent enzyme. IDA in iodine replete area (IRA) have not beenreported. Assesments IDA (Hb), free thyroxine (fT4), Thyrotropin hormone (TSH) of reproductivemothers 17-35 years of age were conducted in IRA and non-endemic deficiency iodine area(NEDIA). Casual iodine urin concentration (UIC) of school age children was also assesed toconfirm iodine endemicity of study area. Analysis of risk for anemia according to iodine status andcorrelation hemoglobin and thyrotropin were performed. The study area was confirmed to be nonendemic iodine deficiency (UIC criteria). Median EIU were 242 (24-880) µg/L in IRA and 211 (44-387) µg/L in NEDIA respectively. Proportion of EIU less than 100 µg/L in IRA were 5.0 % and inNEDIA 1.2 %. Proporsion of EIU greater than 300 µg/L were 29.6 dan 24.7 persen respectively.The results indicated that study areas were no longer endemic iodine deficiency and the peoplewhere they live consumed iodine tend to excess. These situation may effect on thyroid function asindicated by suppressed TSH and fT4 in normal range. Those two thyroid function parameterssignificantly different in the IRA and NEDIA. The everages serum concentration of TSH in thestudy area were 1,96(1,56-2,36) in IRA compared to 1,38 (1,09-1,67) mUI/L in NEDIA(p=0,23);while fT4 were 1,29 (1,14-1,44) and 0,98 (0,90-1,05) µg/dL respectively. Hemoglobin serumconcentration of mothers in those two area was not signicantly different; 12,45 (12,19-12,71) inIRA compared to 12,21 (11,96-12,46) mg/dL di NEDIA. Iron deficiency anemia was found 23,3 %in IRA and 35,7 % in NEDIA; however mothers in IRA have risk for anemia as big as mothers inNEDIA OR: 0,54(0,24-1,24). Analysis correlation (Spearman’s) between TSH and Hb providedcoefisient correlation Rho as much as 0.072 indicated very weak correlation between the twoparameters. There were no difference in proportion of hypothyroidism in the two study areas (OR:0,68 (0,207-2,25). Although the proportion of iron deficiensi anemia (IDA) in IRA much less thanthe proportion in NEDIA; there were no relationship between IDA and Iodine deficiency.Absorption of Fe in IRA may be more efficient than did in NEDIA. More studies are needed toconfirm this finding.Keywords: IDA, TSH, fT4, Hb, EIU, NEDIA, IRA